2023
DOI: 10.1038/s41598-023-32114-5
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun proteomics of quinoa seeds reveals chitinases enrichment under rainfed conditions

Abstract: Quinoa is an Andean crop whose cultivation has been extended to many different parts of the world in the last decade. It shows a great capacity for adaptation to diverse climate conditions, including environmental stressors, and, moreover, the seeds are very nutritious in part due to their high protein content, which is rich in essential amino acids. They are gluten-free seeds and contain good amounts of other nutrients such as unsaturated fatty acids, vitamins, or minerals. Also, the use of quinoa hydrolysate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 87 publications
(137 reference statements)
0
5
0
Order By: Relevance
“…In total, 21 of the 41 genes were annotated with functions and GO terms, with 40% of them directly related to reproduction or seed development (Table S6 ). We used publicly available shotgun proteomics (Poza‐Viejo et al ., 2023 ) and transcriptomics (Grimberg et al ., 2022 ) data from quinoa seeds to assess the expression of the 41 candidate genes. Our results showed that 27 of the 41 candidates could be detected in the proteome and 39 of the 41 candidate genes could be detected in the transcriptome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 21 of the 41 genes were annotated with functions and GO terms, with 40% of them directly related to reproduction or seed development (Table S6 ). We used publicly available shotgun proteomics (Poza‐Viejo et al ., 2023 ) and transcriptomics (Grimberg et al ., 2022 ) data from quinoa seeds to assess the expression of the 41 candidate genes. Our results showed that 27 of the 41 candidates could be detected in the proteome and 39 of the 41 candidate genes could be detected in the transcriptome.…”
Section: Resultsmentioning
confidence: 99%
“…We analysed these genes for similarity and found that no gene within the identified cytochrome P450 gene cluster on CquChr18 is an ortholog of CYP76AD1. Along this line, we could not detect quinoa CYP76AD1 expression in recently published shotgun proteomics data from quinoa seeds (Poza‐Viejo et al ., 2023 ). Thus, our data link seed colour to a novel cytochrome P450 gene cluster that is unrelated to CYP76AD1.…”
Section: Resultsmentioning
confidence: 99%
“…Chitinases are known to play a pivotal role in several abiotic stress responses in plants, encompassing phenomena such as wounding, osmotic stress, cold, heavy metal stress and salt stress. These enzymes have a crucial role in both defense-related systems and the improvement of abiotic stress tolerance in plants ( Liu et al 2020 ; Vaghela et al 2022 ; Poza-Viejo et al 2023 ). Further information can be obtained from a complicated network by identifying important hubs and modules while taking into account network characteristics such as relative graphlet frequency distribution, degree distribution, diameter and clustering, ( Pržulj et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, over the last 20 years, there has been increasing interest in using mass spectrometry for proteins to elucidate the relationship between proteins and specific molecular interactions [ 14 ]. Several reports on the use of Shotgun proteomics have been conducted to study complex peptide fractions generated after protein proteolytic digestion in plants, including leaves of common bean [ 15 ] and seeds of barley [ 16 ], pea [ 17 ], Brassica [ 18 ], and quinoa [ 19 ]. However, some of the recent advances in the proteomics field, such as shotgun proteomics, have yet to be explored in species used in improving abiotic stress tolerance.…”
Section: Introductionmentioning
confidence: 99%